A drónrepüléssel összefüggő magánjogi igények - Zsurzsa, Zsolt (Debreceni Jogi Műhely, 2019)
The technology of unmanned aerial vehicles (UAVs), which are most commonly known as ‘drones’, is one of the most rapidly developing field of modern science. That is largely owing to the fact that drones are used in more and more fields of economy, from architecture and media to agriculture and logistics, etc. According to predictions of the European Union, the drone industry may have an income of € 10 billion annually, by 2035, and could create about 100,000 workplaces as well.[2] In addition, the number of hobby drone users is also increasing quickly, with millions of registered drone users in the United States of America alone.[3]The nature of drones, namely the fact that these devices can soar up to 30 or more metres in the air and carry out different kind of operations (including taking photographs) by an operator on the ground may cause a lot of conflicts between drone operators and people not taking part in the operation. However, these conflicts, are unlikely to be solved without legal interference, which makes it necessary for both lawmakers and organizations applying the law to prepare for these situations in order to be able to give proper answers to the problem.In my research, I have indicated the development of drones in a historical context and also specified the classification of drones, which allowed me to outline those types that are relevant to the subject matter. I also presented the legal background of drone flight in force, on the level of the EU legislation and also gave an insight to the previous, Hungarian legislation. Then, I started to identify those legal claims that can be especially relevant on the terrain of civil law, and concluded three main claims can be named: liability for damages, infringement on personal rights (right to one’s image and, in particular) and the civil tort of trespass to land.I analysed all of these claims separately and in connection with each other, and found interesting problems that could have huge relevance in a legal dispute before a court. I intended to support my findings and arguments with opinions from legal scientists, court decisions from Hungary and abroad, and legislative solutions from abroad. At the end of my writing, I concluded that the described problems, and the solution that is given to them, are indeed crucial, because they will most definitely affect the way people can use drones, and neither too strict, nor too loose rules are appropriate to decide upon the subject.